The Influence Of Education And Training On Work Productivity in Micro, Small and Medium Enterprises (MSMES) in Tentena City - Yohanes Pasambaka; Abdi Sakti Walenta (Pinisi Business Administration Review, 2020)
This research aims to determine the positive relationship and the influence of education and training to work productivity of employees at Pamona Puselemba sub-district of Poso. This type of research is done is quantitative research with descriptive statistics to process the data.The result of this research show that there was a significant relationship between education and training to work productivity, it is obtained from the calculation using the Pearson product moment correlation where the value of rhitung> rtable value or 0.560> 0.497 and there are positive influence where the value thitung> ttable or (2.700> 2.131.